Authority concerned by a prospective notary of internship in developing assets reviewed from Law Number 2 Of 2014 concerning notary positions - Maria Ulfah, (Technium Social Sciences Journal, 2021)
The type of research used in this research is normative legal research or what is said to be juridical normative. At this time Candidates for Notary Officers who will become trusted officials must be truly competent in their field, therefore a prospective notary public is obliged to carry out an internship at the notary's office. The apprenticeship process is very necessary for a prospective notary to know what work will be carried out by the notary who will serve him, this is in the interest of the prospective notary public himself. If you look at this, then the series and stages that must be carried out by a Nataris candidate in the apprenticeship process, of course, have obligations as stated in Law of the Republic of Indonesia Number 2 of 2014 concerning the Position of Notary Public (UUJN), where the obligation is enforced in Article 16A of the UUJN, in among others: (1) Notary candidates who are currently doing an apprenticeship are obliged to carry out the provisions referred to in Article 16 paragraph (1) letter a; (2) Apart from the obligations as referred to in paragraph (1), a prospective Notary Public is also obliged to keep confidential everything concerning the Deed that he has drawn up and all information obtained for making the deed. Notary as a public official in carrying out his profession is obliged to provide legal services to the public, which is useful for obtaining legal protection or protection and guarantees in order to achieve legal certainty. This means that the notary guarantees that the deed made before him is guaranteed the confidentiality in accordance with the oath of office as a notary, that I will keep the contents of the deed and the information obtained in the exercise of my office confidential, as in Article 54 paragraph (1) UUJN, namely that notaries can only provide, show, or convey the contents of the Deed, Grosse, Copy or Quote of the Deed, to a person with a direct interest in the Deed, heir, or someone who has the right, unless otherwise stipulated by statutory regulations.